Adverse Events After Atherectomy: Analyzing Long‐Term Outcomes of Endovascular Lower Extremity Revascularization Techniques. Issue 12 (18th June 2019) - Ramkumar, Niveditta; Martinez‐Camblor, Pablo; Columbo, Jesse A.; Osborne, Nicholas H.; Goodney, Philip P.; O'Malley, A. James
Abstract : Background: The long‐term effectiveness of atherectomy treatment for peripheral arterial disease is unknown. We studied 5‐year clinical outcomes by endovascular treatment type among patients with peripheral arterial disease. Methods and Results: We queried the Medicare‐linked VQI (Vascular Quality Initiative) registry for endovascular interventions from 2010 to 2015. The exposure was treatment type: atherectomy (with or without percutaneous transluminal angioplasty [PTA]), stent (with or without PTA), or PTA alone. The outcomes were major amputation, any amputation, and major adverse limb event (major amputation or any reintervention). We used the center‐specific proportions of atherectomy procedures performed in the 12 months before a patient's procedure as the instruments to perform an instrumental‐variable Cox model analysis. Among 16 838 eligible patients (median follow‐up: 1.3–1.5 years), 11% underwent atherectomy, 40% received PTA alone, and 49% underwent stenting. Patients receiving atherectomy commonly underwent femoropopliteal artery treatment (atherectomy: 65%; PTA: 49%; stenting: 43%; P <0.001) and had worse disease severity (Trans‐Atlantic Inter‐Society Consensus score [TASC] B and greater; atherectomy: 77%; PTA: 68%; stenting: 67%; P <0.001). The 5‐year rate of major adverse limb events was 38% in patients receiving atherectomy versus 33% for PTA and 32% for stenting (log rank P <0.001). Controlling for unmeasured confounding using instrumental‐variable analysis, patients treated with atherectomy experienced outcomes similar to those of patients treated with PTA, except for a higher risk of any amputation (hazard ratio: 1.51; 95% CI, 1.08–2.13). However, compared with stenting, atherectomy patients had a higher risk of major amputation (hazard ratio: 3.66; 95% CI, 1.72–7.81), any amputation (hazard ratio: 2.73; 95% CI, 1.60–4.76), and major adverse limb event (hazard ratio: 1.61; 95% CI, 1.10–2.38). Conclusions: Atherectomy is used to treat severe femoropopliteal and tibial peripheral arterial disease even though long‐term adverse outcomes occur more frequently after this treatment modality.